Implementation of HSV Algorithm for Speed Synchronization of Robot Arm and Conveyor - LILANSA, NOVAL; SURYATINI, FITRIA; WAHIDIN, DEDE MOCH. DINAR (Institut Teknologi Nasional, Bandung, 2025)
Conveyors and robotic arms are often combined in industries for pick-and-place applications. In pick-and-place operations involving a moving conveyor and a robotic arm, accuracy in performing the task heavily depends on the object's coordinate position and the conveyor's speed. This study proposes using the HSV (Hue, Saturation, Value) algorithm and a webcam to synchronize the speed between the robotic arm and the moving conveyor. The HSV algorithm detects objects based on color and enables high-accuracy conveyor speed calculation. The research results show that the system can perform pick-and-place operations with a 90% success rate across various object coordinate positions and different conveyor speeds. Implementing the HSV algorithm provides an efficient solution to enhance accuracy in pick-and-place operation systems.